2017
DOI: 10.1038/sc.2017.84
|View full text |Cite
|
Sign up to set email alerts
|

Key demands and characteristics of occupations performed by individuals with spinal cord injury living in Switzerland

Abstract: Individuals with SCI perform a broad range of occupations that are mainly characterized by cognitive and communicative demands, while physical demands are of minor importance. By informing the development of job matching profiles for vocational guidance, our study facilitates the determination of well-matching jobs for persons with SCI and may contribute to a more sustainable return to work of the affected persons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 31 publications
(41 reference statements)
0
2
0
Order By: Relevance
“…It is supposed to be better to promote vocational retraining towards jobs requiring higher education and assistive technology [14]. Another study analysed the skills for typical jobs after SCI: the participants' occupations predominantly required verbal abilities, complex problemsolving skills and were characterised by conventional work tasks, and social relationships [15]. The authors developed and tested a special tool based on databases for finding a suitable job for unemployed people with SCI and found that this seems to be helpful [16].…”
Section: Discussionmentioning
confidence: 99%
“…It is supposed to be better to promote vocational retraining towards jobs requiring higher education and assistive technology [14]. Another study analysed the skills for typical jobs after SCI: the participants' occupations predominantly required verbal abilities, complex problemsolving skills and were characterised by conventional work tasks, and social relationships [15]. The authors developed and tested a special tool based on databases for finding a suitable job for unemployed people with SCI and found that this seems to be helpful [16].…”
Section: Discussionmentioning
confidence: 99%
“…Citing Janis and Mann (1977), Lazarus and Folkman (1984, p. 142) define problem-solving skills as "the ability to search for information, analyze situation for the purpose of identifying the problem in order to generate alternative courses of action, weigh the alternative course of action with respect to desired or anticipated outcomes, select and implement appropriate plan of action". Need for problem-solving skills for a person with SCI has also been emphasized in a study that was conducted in Switzerland by Nützi and colleagues (Nutzi, Trezzini, Ronca, & Schwegler, 2017). As can be seen in this study, accepting self is a crucial bridge to realizing and applying one's problem-solving skills.…”
Section: Discussionmentioning
confidence: 62%